2014
DOI: 10.1097/01.dss.0000452632.22081.79
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives on Medical Photography in Dermatology

Abstract: We use the results of this study to recommend best practices for photography in dermatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
79
1
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(108 citation statements)
references
References 21 publications
6
79
1
13
Order By: Relevance
“…This is similar to a recent survey of 158 Mohs surgeons, in which all but 4% of respondents collected some form of consent before taking photographs, with the majority preferring verbal over written consent . However, use of verbal consent is at odds to the preferences of surveyed patients, who have expressed a preference for written consent . Written consents are helpful because they clearly state the purpose of image acquisition and limitations of use and serve as a record of the discussion.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is similar to a recent survey of 158 Mohs surgeons, in which all but 4% of respondents collected some form of consent before taking photographs, with the majority preferring verbal over written consent . However, use of verbal consent is at odds to the preferences of surveyed patients, who have expressed a preference for written consent . Written consents are helpful because they clearly state the purpose of image acquisition and limitations of use and serve as a record of the discussion.…”
Section: Discussionsupporting
confidence: 77%
“…Unfortunately, in the absence of guidelines that protect patient safety, some institutions are restricting medical photography's use. This hampers patient care in the name of patient protection, despite empirical evidence that patients themselves overwhelmingly support clinical photography for patient care, teaching and research purposes . It is essential to develop best practices guidelines to protect this crucial component of dermatologic care, education, research and record keeping.…”
mentioning
confidence: 99%
“…The preference for the use of an institution‐owned camera to personal camera/personal camera‐phone for medical photography is consistent with that found in another survey of 338 patients attending oral and maxillofacial surgery and plastic surgery clinics in Nigeria , and in a survey of 400 patients from dermatology settings in New York City . The latter survey also endorsed the preference that the photographs be taken by a physician rather than by a nurse or student .…”
supporting
confidence: 80%
“…A survey of dermatology patients in Chicago revealed that nearly all (98%) patients found the practice of medical photography using a hospital‐owned camera to be acceptable, in contrast to only 27% who found photography using the dermatologist's personal smartphone acceptable . A similar study in New York City reported 91% of patients being comfortable with photography using a clinic‐owned camera compared to 32% who were comfortable with photography using a mobile device . The main concerns reported by patients related to confidentiality .…”
Section: Discussionmentioning
confidence: 99%